Be Aware Not Reactive: Testing a Mediated-Moderation Model of Dark Triad and Perceived Victimization via Self-Regulatory Approach - Khan, Hira Salah ud din; Zhiqiang, Ma; Siddiqui, Shakira Huma; Khan, Muhammad Aamir Shafique (Frontiers in Psychology, 2020)
Generally toxic employees are under performers, yet some get better salaries and excel at workplace, getting positioned at higher ranks. This research assesses the relationship between the dark triad (Narcissism, Machiavellianism, and Psychopathy) and perceived victimization with a focus on the mediating effect of abusive supervision and the moderating effect of mindfulness. The data were gathered in three waves. Both the structural equation model with partial least square and Process were used to analyze the data. The study findings suggest that abusive supervision plays a mediating role in the association between the dark triad and perceived victimization. However, the results did not support the mediating role of abusive supervision in the association between narcissism and perceived victimization. Moreover, the findings suggest that mindfulness weakens the effect of abusive supervision on perceived victimization. Furthermore, our findings support the mediated-moderation model. Theoretical and practical implications of the results are also discussed.